At a meeting of the true Sons of Liberty, in the city of New-York, July 27, 1774, properly convened : Present, John Calvin, John Knox, Roger Rumpus, &c. &c. &c. 1. Resolved, that in this general time of resolving, we have as good a right to resolve as the most resolute . - Snuffle, Ebenezer (LLMC-digital (Series), 1774)
Fifteen satirical resolutions. Signed: By order of the meeting, Ebenezer Snuffle, secretary.